EFFECTS OF THE GOODS AND SERVICES TAX (GST) ON DAIRY FARMING. - 1. Rohit Patel , 2. Dr. Jaikishan Sahu (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Dairy Farming is a major source of income for a large population in India. As majority of farmers in the country have marginal and small landholdings, animal husbandry helps them to sustain their livelihood. The Goods and Services Tax (GST) which came into force from July 2017 is a single indirect tax introduced after merging various indirect taxes of the state and Central Government. The effects of the new tax regime can be seen on all sectors including the rural sector. The GST rates on Dairy equipment’s, dairy inputs like hay, cattle feed have increased from the past tax regime which has significantly affected the profitability and operations of the dairy farmers. This study is conducted in Harda district of Madhya Pradesh which is a major agricultural area of Central India. Both Primary and Secondary data is used for the study to know the outcomes of the new tax regime. Primary data is collected from 75 respondents of Harda district of Madhya Pradesh. Secondary data is collected through various journals and websites. Chi-square test is used to test the hypothesis.